Влияние формы беговой дорожки на контактное взаимодействие с шаровыми поршнями радиальной гидропередачи - Скрипченко, Наталья Борисовна; Ткачук, Анна Владимировна; Ткачук, Николай Николаевич; Касай, Елена Игоревна; Крылюк, Богдан Иванович (НТУ "ХПИ", 2015)
С целью определения влияния формы беговой дорожки на контактное взаимодействие со сферическим поршнем гидропередачи разработан вариант метода граничных элементов. С использованием параметрической модели исследовано влияние формы профиля беговой дорожки и податливости слоя шероховатости на распределение контактных давлений. Установлены характерные особенности конфигураций контактных площадок и распределения контактных давлений.

A modification of the boundary element method has been developed for the analysis of the relation between the geometry of the running track and its contact interaction with a spherical piston of a hydrovolumetric drive. A parameterized model provided information about the influence of the geometrical profile of the running track and the compliance of the rough contact layer upon the distribution of the contact pressure. Characteristic configurations of contact areas and contact pressure distributions have been identified.
Influence of the geometry of the running track on its contact interaction with a spherical piston of a hydro-volumetric drive
Keywords: давление контактное; податливость; шероховатость; метод граничных элементов; contact interaction; contact pressure; compliance; roughness; boundary element method